(untitled) (Journal of Applied and Natural Science, 2015)
Hematological parameters have been recognized as valuable tools for monitoring fish health. The aim of the present study was to obtain a basic knowledge of the hematological responses of different groups of fresh water teleosts during acclimation period. Haematological analysis was carried out in three different groups of teleosts namely Group I: Heteropneustes fossilis and Clarias gariepinus (Siluriformes), Group II: Anabas testudineus and Channa striatus (Perciformes), Group III: Labeo rohita and Cyprinus carpio (Cypriniformes). In all groups of teleosts, RBC and Hb were significantly (p<0.05) decreased after 7 days of captivity in response to stress factors raised in capture, handling and sampling procedure. WBC was found to be significantly (p<0.05) increased in group I (Siluriformes), group II (Perciformes) and group III (Cypriniformes) of teleosts after 7 days of captivity due to enhanced production of leucocytes in the hematopoietic tissue of the kidney and the spleen. RBC count and WBC count were found to be higher in H. fossilis and C. gariepinus than other groups of teleosts due to their active predacious nature. Hb values were high in 2nd group (Perciformes) consisting of A. testudineus and C. striatus by virtue of their possessions of accessory respiratory organs. PCV, MCV and MCHC were significantly (p<0.05) increased in three groups of teleosts during acclimation and values were high in second group of consisting of A. testudineus and C. striatus. MCH was higher in 3rd group of fishes consisting of L. rohita and C. carpio.